Hábitat productivo, progresivo y sostenible; prototipo de vivienda rural para la vereda La Falda, Timaná (2021)
Rurality is a fundamental issue for a country whose agricultural sector is the livelihood for a large percentage of the population, such as Colombia; different issues in this sector have caused the peasant population to have difficulties in the development and progress of life in the countryside, more specifically in housing aspects. The municipality of Timaná, to the south of the department of Huila, has a considerable lack of habitability, particularly in qualitative aspects of rural housing, where different phenomena were taken into account when carrying out this work, one of them being the fragmentation of the land that has led to a series of events that are reflected in the lives of the peasants, involving economic and productivity issues that prevent families from projecting improvements in their homes